Prophetic Parenting; The Role of Parents in Building The Character of Children in Madrasah - Raihanah, Raihanah (JURNAL AL-TANZIM, 2022)
This study aims to find out about the role of parents in building children's character at MAN 1 Banjarmasin. This research uses a qualitative case study approach, where the researcher uses interviews, observation, and documentation as the primary media to obtain data. The data analysis was carried out simultaneously, starting with data reduction, displaying data to concluding. The results showed that the role of parents in building children's character at MAN 1 Banjarmasin was done through; the formation of the nature and character of parents, preparing excellent schools as places for children to be educated and forged, directions, rules, and prohibitions, and become good friends of children. This research has implications for the importance of parental leadership in building solid religious characters in children. They do not falter when hit by the storms of globalization and modernization.